Development of a Driver Information System Based on On-board Diagnostic II Communication Protocol - Zakaria, Mohamad Fauzi (2007)
An On-Board Diagnostic II (OBD-II) is a standard diagnostic software management that is installed in a Powertrain Control Module (PCM). It provides some useful data to the driver. There are four different devices using the OBD-II protocol exists in the market that can be used as a driver information system. They are personal digital assistant Dyno/OBD-II scan tool, CarChip Fleet, DriveRight 600, and ScanGauge II. Each of these four devices has some limitation in term of supporting all features for live data monitoring, diagnostic trouble code scanning, trip information, and data logging system. Thus, there is a need for a device that supports all these features together with scheduled service reminder. This thesis describes the design and development of a driver information system based on OBD-II protocol. Its hardware and software systems were designed based on four design considerations: upgrade capability, high data storage capacity, back-up capability, and user friendly. The proposed system consists of an 8-bit microcontroller, a buffer memory, a liquid crystal display, a real time clock, a MultiMediaCard, an OBD-II interpreter unit, and power supply unit. This system was successfully interfaced and tested with the PCM of Hyundai Getz car.